INTEGRATION OF ALGEBRA AND CHEMISTRY CONCEPTS WITH MOLECULAR DESCRIPTORS: A PROBLEM-BASEDLEARNING EXERCISE (2018)
A problem-based learning experience integrating mathematical concepts of linear and abstract algebra for undergraduate chemistry students is presented. The pedagogical framework was focused on the conceptual understanding of the vector space, graph theory and matrix algebra as a tool to obtain chemical information. The students were capable to solve a problem of physicochemical properties prediction through the calculation of molecular descriptors of the TOMOCOMD (acronym for TOpological MOlecular COMputational Design) approach. A “scientific congress” was organized by students to expose the results of the research. This evaluation strategy stimulated the self- and co-evaluation. The proposed experience demonstrated an enhanced learning compared to the traditional model.